Evaluation of the Hypoglycemic Activity of Morchella conica by Targeting Protein Tyrosine Phosphatase 1B - Begum, Naeema; Nasir, Abdul; Parveen, Zahida; Muhammad, Taj; Ahmed, Asma; Farman, Saira; Jamila, Nargis; Shah, Mohib; Bibi, Noor Shad; Khurshid, Akif; Huma, Zille; Khalil, Atif Ali Khan; et al. (Frontiers in Pharmacology, 2021)
Morchella conica (M. conica) Pers. belongs to six wild edible mushrooms that are widely used by Asian and European countries for their nutritional value. The low glycemic index of mushrooms makes them the best source for drug development against diabetes. The present study assessed the anti-diabetic potential of M. conica methanolic extract (100 mg/kg body weight) on streptozotocin (STZ)-induced diabetic mice. STZ was used in a single dose of 65 mg/kg to establish diabetic models. Body weights, water/food intake and fasting blood glucose levels were measured. Histopathological analysis of the pancreas and liver were performed to evaluate STZ-induced tissue injuries. In addition, in-vitro assays such as α-amylase and protein tyrosine phosphatase 1B (PTP1B) inhibitory, antiglycation, antioxidant and cytotoxicity were also performed. The in-vitro study indicated potent PTP1B inhibitory potential of M. conica with an IC50 value of 26.5 µg/mL as compared to the positive control, oleanolic acid (IC50 36.2 µg/mL). In-vivo investigation showed a gradual decrease in blood sugar level in M. conica treated mice (132 mg/dl) at a concentration of 100 mg/kg as compared to diabetic mice (346 mg/dl). The extract positively improved liver and kidney damages as were shown by their serum glutamic pyruvic transaminase (SGP), serum glutamic oxaloacetate (SGO), alkaline phosphatase (ALP), serum creatinine and urea levels. Histopathological analysis revealed slight liver and pancreas improvement of mice treated with extract. Cytotoxicity assays displayed lower IC50 values. The study concludes that in-vivo antidiabetic potential of M. conica and its correlation with altered expression of PTP1B in liver and pancreas might be due to the presence of compounds responsible for the activity against diabetes showed by the LC-MS analysis of M. conica.